Nonlinear Analysis and Variational Problems In Honor of George Isac - Pardalos, Panos M.; Rassias, Themistocles M.; Khan, Akhtar A. (Springer Optimization and Its Applications, 2010)
The chapters in this volume, written by international experts from different fields of mathematics, are devoted to honoring George Isac, a renowned mathematician. These contributions focus on recent developments in complementarity theory, variational principles, stability theory of functional equations, nonsmooth optimization, and several other important topics at the forefront of nonlinear analysis and optimization. "Nonlinear Analysis and Variational Problems" is organized into two parts. Part I, Nonlinear Analysis, centers on stability issues for functional equations, fixed point theorems, critical point theorems, W*-algebras, the Brezis-Browder principle, and related topics. Part II, Variational Problems, addresses several important aspects of optimization and variational methods. This includes equilibrium problems, projected dynamical system, set-valued and set-semidefinite optimization, variational inequalities, variational principles, complementarity problems, and problems in optimal control. In the last few decades, the theory of complementarity, functional stability and variational principles have provided a unified framework for dealing with a wide range of problems in diverse branches of pure and applied mathematics, such as finance, operations research, economics, network analysis, control theory, biology, and others. This volume is well-suited to graduate students as well as researchers and practitioners in the fields of pure and applied mathematics, social sciences, economics, operations research, engineering, and related sciences.